Impact of financial fraud on the financial security of households (Economics and region, 2025)
Financial fraud represents a significant and dangerous socio-economic threat to the stability of contemporary Ukrainian society. Its impact has grown substantially in the context of martial law and the widespread adoption of digital technologies. The aim of this study is to examine the consequences of financial fraud on the financial security of households. Specifically, it seeks to understand how fraudulent practices affect citizens’ cognitive abilities, increasing their vulnerability to emerging forms of deception. The central hypothesis of this paper is that the socio-economic instability of part of the population, combined with low levels of financial literacy and a general distrust of institutions, creates conditions conducive to the spread of financial crimes in Ukraine. The theoretical value of the research lies in its contribution to a deeper understanding of the mechanisms of social deception in the context of an information-saturated society. Through the analysis of the interplay between vulnerability, knowledge gaps, and the erosion of trust, the study aims to deepen the academic understanding of how individuals become susceptible to financial manipulation. The practical significance of this work lies in the development of recommendations to enhance the financial security of households, including improving financial literacy, fostering critical thinking skills to identify and resist fraudulent schemes, and the need for legislative initiatives that clearly define the responsibilities of financial institutions in combating dishonest practices. The scientific novelty of the article stems from its integrated approach, combining financial and legal analysis of the phenomenon of fraud and its direct impact on the financial security of households. This interdisciplinary approach offers a more comprehensive understanding of the issue. Future research, building on the insights of this study, will focus on empirically testing the hypotheses through rigorous examination of representative samples of the Ukrainian population, further refining and substantiating the theoretical framework.
Keywords: financial fraud; trust; financial vulnerability; social engineering; psychological manipulation; financial literacy; telephone fraud; financial security